Variation in Structure and Quality of Some Indian Timbers in Relation to Growth - Ghosh, S. S.; Ramesh Rao, K.; Purkayastha, S. K. (Indian Forester, 1958)
Variations in structure and quality of some Indian hardwoods are discussed with special reference to rate of growth. Though considerable work has been done in India and other countries on non-porous and ring-porous woods, hardly any information is available on diffuse-porous woods. As Indian timbers mostly belong to this group an attempt has been made in this paper to bring out some salient trends, observed at the Forest Research Institute, Dehra Dun, which may be of interest to workers in other tropical countries.